Impact of Changing Stellar and Planetary Magnetic Fields on (Exo)planetary Environments and Atmospheric Mass Loss - Sakshi Gupta; Arnab Basak; Dibyendu Nandy (The Astrophysical Journal, 2023)
The magnetic activity of a star—which modulates the stellar wind outflow—shapes the immediate environments of orbiting (exo)planets and induces atmospheric loss, thereby impacting their habitability. We perform a detailed parameter space study using three-dimensional magnetohydrodynamic simulations to understand the effect of changing stellar wind magnetic field and planetary magnetic field strengths on planetary magnetospheric topology and atmospheric losses. It is observed that the relative strengths of stellar and planetary magnetic fields play a significant role in determining the steady-state magnetospheric configuration and atmospheric erosion. When the stellar field is strengthened or the planetary field is weakened, stellar magnetic field accumulation occurs at the dayside of the planet, forcing the magnetopause to shift closer to its surface. The magnetotail opens up, leading to the formation of Alfvén wings in the nightside wake region. We demonstrate how reconnection processes and wind conditions lead to the bifurcation of the magnetotail current sheet. With increasing stellar wind magnetic field strength, the dayside reconnection point approaches the planet, thereby enhancing mass loss. We establish an analytic equation relating the atmospheric mass-loss rates to stellar and planetary magnetic field strengths, which successfully explains the modeled behavior. Our results are relevant for understanding how the interplay of stellar and planetary magnetism influence (exo)planetary environments and their habitability in star–planet systems with differing relative magnetic field strengths or in a single star–planet system over the course of their evolution with age.